Kargopol’s Private Museums of the Arkhangelsk Region and the Surrounding Area: the Phenomenon in the Context of the Development of Ethnic Tourism in the Region - Shevelyova, Elizaveta V. (Actual Problems of Theory and History of Art, 2013)
Kargopol and its surroundings have got rich history and monuments with strong cultural and natural potential. The article deals with the phenomenon of private museums active for 10‒15 years in the context of tourism as a priority task of the region’s development. The author makes an attempt to classify them, identify the main areas of activity and their perspectives.
Keywords: private museums; Kargopol; Arkhangelsk region; Russian folk art; traditional culture; ethno-tourism